Epigenetic Regulations of Perineural Invasion in Head and Neck Squamous Cell Carcinoma - Hurník, Pavel; Chyra, Zuzana; Ševčíková, Tereza; Štembírek, Jan; Trtková, Kateřina Smešný; Gaykalova, Daria A.; Buchtová, Marcela; Hrubá, Eva (Frontiers in Genetics, 2022)
Carcinomas of the oral cavity and oropharynx belong among the ten most common malignancies in the human population. The prognosis of head and neck squamous cell carcinoma (HNSCC) is determined by the degree of invasiveness of the primary tumor and by the extent of metastatic spread into regional and distant lymph nodes. Moreover, the level of the perineural invasion itself associates with tumor localization, invasion’s extent, and the presence of nodal metastases. The etiology of HNSCC is typically linked to tobacco and alcohol abuse or to human-papillomavirus infection. Here, we summarize current knowledge about different aspects of epigenetic changes, which can be associated with HNSCC while focusing on perineural invasion (PNI). We review individual enzymes involved in epigenetic abnormalities known as diagnostic markers in HNSCC and their involvement in processes contributing to perineural invasion. We also focus on key genes participating in the induction of PNI and their epigenetic status in HNSCC. Understanding epigenetic regulations of axon growth that lead to tumorous spread or uncovering the molecular control of axon interaction with cancer tissue can help discover new therapeutic targets for these tumors.